COMPREHENSIVE TREATMENT FOR CHILDREN 6 YEARS OLD WITH EARLY CHILDHOOD CARIES - Fidya Kemala Putri; Jeffrey Jeffrey (Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2020)
Background : Dental caries is still one of the most common problems in Indonesia, not only in adults but also in children. The prevalence of dental caries in Indonesian primary schools is almost 60-80%. Caries is a multifactorial disease caused by host (teeth), microorganism, carbohydrates, and time. Early childhood caries (ECC) is one of the most prevalent diseases in children worldwide. ECC driven by oral microorganism which is mainly caused by sugar rich-foods. In addition, poor oral hygiene and  removal of dental plaque leads to the rapid development of ECC.The goal of this treatment is to prevent malocclusion of the teeth and maintain the growth and development of the child. Case report : A6-year-old girl with ECC and poor oral hygiene is given comperhensive treatment, such as restoration, endodontic treatment, extraction and space management. Conclusion: Comperhensive treatment was successful and both patient and parent were satisfied with the treatment.This can be seen from the plaque control of the child before and after the toothbrush during the visit and the space available for replacement teeth is sufficient. The pre-toothbrush control at the February 2020 visit was 25% and then the toothbrush 19%, which were 75% and 35.5% previously.